Indo-US Nexus to Isolate Pakistan: Options and Responses - Ashfaq Ahmad Malik; Dr. Nazir Hussain (Journal of Political Studies, 2018)
India-Pakistan conflict is one of the most complicated and protracted conflicts in modern time, clouded by historical, ideological, religious, and political sentimentality. Beyond these, the diplomatic uncertainty between the two countries has proven to be capable of being transnational and international. Following the Indo-US strategic alliance, there is a growing perception that New Delhi is increasingly demonstrating and deepening its hegemonic designs in South Asia and beyond. Under the BJP government, such hegemonic proclivity has exacerbated the mistrust and the gulf of understanding between New Delhi and Islamabad. With the blessing of Washington, the BJP government has changed the dynamic of the mistrust. To this end, the paper addresses the current dynamics twofold. The first part of the paper looks at Modi’s effort geared at isolating Pakistan, the second discusses the mutual effort of Modi and Trump to politically and diplomatically ostracise Pakistan within the comity of nations. The last part of the paper discusses the three ways Pakistan should respond to the individual and combine efforts of Modi and Trump.